Fast excitation control strategy for typical magnetically controllable reactor for reactive power compensation. (July 2021) - Mehmood, Kashif; Li, Zhou; Tahir, Muhammad Faizan; Cheema, Khalid Mehmood
Highlights: Improve the response speed of the Magnetically Controllable Reactor. Rapid Magnetization and demagnetization strategy for slow response Magnetically Controllable Reactor. The strategy to improve the response speed without changing the structural windings of the Magnetically Controllable Reactor. The proposed strategy is suitable for all the traditional Magnetically controllable reactor used in UHV transmission lines. Abstract: Though the magnetically controllable reactor (MCR) has been used in dynamic reactive power compensation of high voltage long distance transmission lines, its dynamic compensation performance is restricted by the imperfection of its slow response in the transition process. Hence, based on the typical structure and working principle of MCR, a novel fast excitation control based on rapid magnetization and demagnetization (RMDM) strategy, which only needs to add augmented boost circuit in the control winding of an MCR, is proposed to improve the dynamic response characteristics of MCR. The mathematical model of the novel proposed RMDM strategy is built and analyzed, based on which, the associations between the estimated transition time and the parameters of the typical MCR structure with auxiliary circuit are considered. Furthermore, the simulation model of the RMDM strategy is established by PSCAD/EMTDC, and simulation findings indicated that the transient time of magnetization and demagnetization of the typical MCR is improved from 0.5sec and 1.0sec to 0.3 sec and 0.1 sec respectively, while the transient time of the reactive power compensation is improved by half. These results substantiate the precision of the theoretical analysis and efficacy of the proposed RMDM strategy of typical MCR.